Diagnostic Accuracy of Sonographic Findings of Intestinal Intussusception in Paediatric Population with Surgical Outcomes as Gold Standard - Sandhu, Ayesha Ijaz; Abdullah, Muhammad Faraz; Habib, Tayyaba; Arif, Hira (Indus Journal of Bioscience Research, 2025)
Background: Intestinal intussusception in children is an emergent condition requiring early diagnosis and management to prevent complications. While initially less invasive and more cost-effective ultrasound is commonly utilized for detection, the sensitivity of ultrasound for diagnosis of intussusception in relation to surgical exploration is an area that needs further study. Objective: To determine the diagnostic accuracy of sonographic findings in identifying intestinal intussusception in the pediatric population, with surgical outcomes serving as the gold standard for comparison. Study Design: This is a cross-sectional validation study conducted at the Department of Diagnostic Radiology, Ali Fatima Hospital, Lahore. Duration and Place of Study: The study was conducted from August 2024 to February 2025. Methodology: The study included 216 pediatric patients under 12 years of age, presenting with clinical symptoms indicative of intussusception, including colicky abdominal pain, vomiting, and red jelly-like stools. Ultrasound was performed using a Philips EPIQ 7G machine, and the results were compared with surgical outcomes. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated to determine the diagnostic accuracy of ultrasound. Results: The study found that ultrasound had a sensitivity of 82.5%, specificity of 50%, diagnostic accuracy of 73%, PPV of 80.1%, and NPV of 53%. Stratified analysis showed variability based on age, gender, and symptom duration. Ultrasound demonstrated higher sensitivity in patients older than 6 years (100%), while specificity decreased to 0%. Conclusion: Ultrasound is a moderately effective diagnostic tool for intussusception in pediatric patients.